Molecular characterizacion of Trichoderma spp. in pea Pisum sativum L. - Checa C., Oscar Eduardo; Descance V., Jessica Andrea; Toro C., Maribel Xiomara; Álvarez, Sandra Lorena; Salazar G., Claudia (Revista de Ciencias Agrícolas, 2016)
The genetic variability of Trichoderma spp isolates was determined through RAPD markers. A high polymorphism was found with primers OPB 01, OPC 01, OPA 03, OPD 05, and OPA 01. The observed molecular variation was low (26%) among Trichoderma spp populations, which were identified by their geographical origin as Ipiales, Pupiales, and Gualmatán. In contrast, variation within populations was high, exceeding 70%. The Trichoderma spp. species showed no relationship with their geographical origin. The isolates were grouped based on Jaccard’s genetic diversity. The range of genetic distance between the different isolates was between 0.37 and 1.42. The most frequent species was T. harzianum, which showed a high variation in all clusters.